PENENTUAN WAKTU TANAM PADI SAWAH DI KABUPATEN SANGIHE DENGAN MENGGUNAKAN MODEL SIMULASI SHIERARY RICE - Fattah, Farida; Rogi, J. E.X.; Toding, Mariam M. (EUGENIA, 2015)
ABSTRACT Decline in rice production in Sangihe Island partly due to climate change and the implementation of a less precise planting time. Rice Shierary model was used to predict the timing of planting paddy and has advantages in time and cost savings. This study aims to determine the exact time of planting in paddy rice crops in the district of South Manganitu, North Tabukan and Tamako, as well as to determine whether the results of the simulation model Shierary Rice together with the results obtained from the Central Bureau of Statistic Sangihe Islands. Input model consists of solar radiation, rainfall, temperature and humidity, field capacity, permanent wilting point, varieties, irrigation, nitrogen fertilization, longitude and latitude of the study area. While the output was paddy rice yield potential. It can be concluded that (a) the appropriate planting time of paddy in the South Manganitu namely in June with a potential yield of 4.25 tonha-1 and March with a potential yield of 3.88 tonha-1. (b) the appropriate planting time of paddy in the North Tabukan namely in June with a potential yield of 4.27 tonha-1 and March with a potential yield of 3.62 tonha-1. (c) the appropriate planting time of paddy in Tamako ie in March with a potential yield of 3.58 tonha-1 and February with a potential yield of 3.28 tonha-1. (d) the yield of rice field paddy with the determination of planting time by using the model of Shierary Rice nearing/line with productivity results which obtained by the Central Statistics Agency (BPS) Sangihe Islands. Keywords: planting, paddy, simulation models, Shierary Rice